Design of a planar corner-reflector - Chen, Yuling (2019)
Antenna is widely used in today’s wireless communication field, especially with the development of new technology, new type of antenna with the properties of high gain, wide bandwidth and retro-directive such as planar corner reflector is needed. Planar corner reflector antenna is a combination of planar reflector antenna and antenna array, which will provide advantages of both antennas, due to its uncomplicated structure, easy and cheap to fabricate and implement, many researches have been done on this topic. The thesis of this report is to investigate a planar corner reflector with different feeding methods. This report will present the whole process of the project implementation. First in this report, the student introduces basic background knowledge of wireless communication, antenna and antenna array, followed up with theoretical analysis to retro-directive array reflector named Van Atta array. In the second half of this project, for each feeding method, after verifying the single patch unit, the student analyzes the planar array in both one dimension and two dimensions with designed antenna array on the software named HFSS. Specific details will be explained in the later part of this report with data and graphics. The designed Van Atta array will be excited under the beam scanning of 10 degrees, 20 degrees, 30 degrees, 40 degrees respectively. After the simulations on the software, the student fabricates and tests on vertical 1x4 array and horizontal 1x4 array, makes comparisons between the results from the simulations in the software and measurements results in the real field not only for designed antennas but also for the perfect electric conductor in the same size. In the end of this report, the student draws conclusions and points out the recommendations for future research work.